Identifikasi Analisis Resiko Keselamatan Kerja pada Proses Pemotongan Menggunakan Grinda dengan Metode Job Safety Analysis (JSA) di PT. XYZ - Aditiya, Machlum; Mustaqim, Mustaqim (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
PT. XYZ is a company operating in the field of Electrical Contractor, Service and Maintenance, Electrical Equipment and Supplies. Grinding and welding carry the risk of work accidents that may occur during work. The aim of this research is to identify the risk of work accidents during grinding at PT. XYZ using the Job Safety Analysis method. The method used in this research is to carry out direct observations to control work safety in order to reduce the impact of the risk of work accidents. The results obtained are the results of the risk assessment in each job, there is a risk of work accidents in the griding section with likelihood and severity values. From the results of risk control in the cutting process, it can be done by means of technical control (repairing or adding technical facilities or equipment such as adding K3 signs).